Three‐level meta‐analysis of the other‐race bias in facial identification - Lee, Jungwon; Penrod, Steven D. (Applied cognitive psychology, 2022)
The current research conducted a three‐level meta‐analysis with a total of 159 journal articles on the other‐race bias in facial identification, which had been published between 1969 and 2021. The effect size analysis yielded moderate pooled effect sizes of the other‐race bias on face identification—people showed higher hit rates and discriminability, lower false alarm rates, and more stringent criteria for own‐race faces than for other‐race faces. Results from the sensitivity analysis and publication bias analysis also supported the robustness of the other‐race bias. In moderation analyses, participant race (White vs. non‐White) and retention interval between the study and test phases produced stable moderating effects on estimates of the other‐race bias. Despite an increase in racial diversity for decades in our society, the current meta‐analysis still demonstrated robust effects of the other‐race bias in facial identification, replicating findings from the previous meta‐analyses.